PENGUATAN KARAKTER DAN KREATIFIKTAS BERBASIS METODE HAPPY LEARNING DALAM PEMBELAJARAN PADA MASA COVID-19 - Adi Haironi; Sutrisno Sutrisno; Sukiman Sukiman (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
The current condition of the world is being exposed to the Covid-19 virus pandemic, so the world community must practice social distancing. In Indonesia, PSBB (Large-Scale Social Restrictions) is also enforced, resulting in very limited activities outside, including in the world of education. The emergence of creative learning ideas that require a teacher to be able to stimulate students, both in the context of creative thinking and in the context of creatively doing something. Creative thinking always starts with critical thinking, namely finding and giving birth to something that didn't exist before or fixing something that wasn't good before. The method used in writing this article is a literature study. By outlining the concepts of creativity to the learning methods used during this pandemic. Starting from the definitions of creativity and character from previous researchers, to the synthesis of creativity, which finally got an operational definition of creativity.